Diversity of bird agroforestry species in Sapen Nusantara Conservation Park of Mount Arjuno, Pasuruan - Endik Deni Nugroho; Dwi Anggorowati Rahayu; Amang Fathurrohman; Roisatul Ainiyah; Zainul Ahwan; Muhammad Dayat; Mulyono Wibisono; Fafit Rahmat Aji; Kasiman Kasiman (Biology Education Department, IKIP Budi Utomo, Malang, Indonesia, 2023)
The Sapen Nusantara Conservation forest park is agroforestry that has certain vegetation. The vegetation in Sapen Nusantara Protected forest park seems to support the existence of birds as wildlife that need a living habitat. The existence of bird species in Sapen Nusantara Protected forest park is very important in supporting agroforestry vegetation. However, until now the diversity of bird species there has not been identified and recorded properly. The forest is one of the buffer forests of Mount Arjuno protection forest, so the ecosystem must be maintained. This study aims to analyze the diversity of bird species in the agroforest forest area in Sapen Nusantara Conservation forest park, Ledug Village, Pasuruan. The research was conducted in July 2021 using the direct observation method (point count) on ecotourism routes by calculating and recording the trails traversed using GPS, sampling by observing walking along the path/road accompanied by predetermined observation points, identification based on MacKinnon et al., (2010) and information on the status of its protection. Data analysis used the Shannon-Wiener diversity index, evenness index, and species richness index. The results of the study identified 18 bird species from 16 families with a total of 169 individuals. Of all the birds found, 18 species are listed in IUCN status, and 4 are listed in the protected status PP No. P.106 of 2018 and 3 species are listed in the CITES category Appendix II. It is known that the Shannon diversity index (H'=2,547) is in the medium diversity category. species evenness index (E=0.9) with a high evenness category and stable community. Then the specific wealth index (R=3.31) with the category of species richness is classified as medium. The presence of birds in the Sapen Nusantara conservation park forest indicates that the ecosystem in the forest is still maintained and this cannot be separated from the role of the community, especially the Ledug Lembaga Masyarakat Desa Hutan (LMDH), which manages and maintains the forest.